CATUR PURUSA ARTHA VS TRI KAYA PARISUDHA ON THE LEVERS OF CONTROL TOWARDS THE PERFORMANCE OF VILLAGE-OWNED BUSINESS ENTITIES - I Made Pradana Adiputra (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
The establishment of BUMDES is one of the efforts to accelerate the management of poverty including in Bali. Fraud cases related to the management of BUMDes funds occur a lot in Buleleng Regency. At least 4 cases out of 6 cases that occurred in Bali Province occurred in Buleleng Regency. This research aims to religious value of Catur Purusa Artha (CPA) and Tri Kaya Parisuda (TKP) on the elements of the management control system, namely the levers of control over the performance of BUMDes in Buleleng Regency. Data collection through primary data collection with questionnaires to BUMDes managers. Data analysis is carried out through a hypothesis testing process that is formulated through an interaction/moderation regression test between levers of control with CPA and TKP on BUMDes performance. The results from 75 questionnaires that can be processed show that both CPA and TKP positively affect the impact of LoC on the performance of BUMDes. Based on the significance value, it proves that CPA has a stronger moderation influence than the crime scene. This shows that CPA is considered to have a stronger role in the personal BUMDes manager in Buleleng Regency in carrying out the organization's operations without disregarding the value of the crime scene as a religious or cultural value in Bali.